Evil and International Relations - Jeffery, R. author. aut Link
VIII, 235 p.
Keywords: This book seeks to determine what is meant by 'evil' when used to describe actors and events in international politics. Focusing on the history of evil in western secular and religious thought, it reintroduces a classical understanding of evil as the means to which we seek to understand otherwise meaningless human suffering.